The Beauty of Japanese Ceramics in Indonesia: from VOC to Edo Shogunate's Falconry (Takagari) - Alpina Pamugari (Universitas Diponegoro, 2025)
The Dutch East India Company (VOC), founded in 1602 (Keicho 7), exported Chinese porcelain to Europe and Southeast Asia. However, a civil war broke out in China with the transition from the Ming Dynasty to the Qing Dynasty, making it impossible to export porcelain. In trouble, VOC turned its attention to Arita, where production was increasing at the time, and concluded an export contract with Japan. At that time, Japan was closed off to the rest of the world, and its only point of contact with other countries was Dejima in Nagasaki. In 1659 (Manji 2), pottery was shipped from Imari Port and headed for Dejima, where it was transferred to a Dutch ship and set off overseas. After this, Imari ware continued to be exported for about 100 years, attracting European royalty and aristocrats. Looking at the Imari Road, a sea route for the ceramic trade that took place in the 17th century, it be found that Old Imari was distributed as far as Indonesia, and when I look at the characteristics of the Japanese ceramics that remain in Indonesia, I can see the 83 example was thought to be Old Imari, and the other porcelain was also thought to be Japanese ceramics. Among them, I picked up the Imari Large Dish with Colored Sakura and Eagle Paintings in Kinrande Style and inferred that this work was intended for export. In the Edo shogunate, the falconry system (takagari) was practiced frequently, and it is thought that the patterns were selected for Edo art works, especially Ko-Imari, which were exported overseas. <a href=